2022
DOI: 10.1055/a-2003-7689
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Microsurgery Training Curriculum

Abstract: Background Microsurgery is one of the most challenging areas of surgery with a steep learning curve. To address this educational need, microsurgery curricula have been developed and validated, the majority focus on technical skill only. The aim of this study was to report on the evaluation of a well-established curriculum using the Kirkpatrick model. Methods A training curriculum was delivered over 5 days between 2017 to 2020 focusing on: 1) microscopic field manipulation, 2) knot tying, non-dominant hand usag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The usefulness of constructing a good educational system for disseminating microsurgical skills has been reported previously. 39 , 40 We believe that the AV-ETS strategy using the MPETS method ensures that preoperative planning and intraoperative procedures are uniform. Hence, the MPETS method is useful for passing on the free flap technique.…”
Section: Discussionmentioning
confidence: 99%
“…The usefulness of constructing a good educational system for disseminating microsurgical skills has been reported previously. 39 , 40 We believe that the AV-ETS strategy using the MPETS method ensures that preoperative planning and intraoperative procedures are uniform. Hence, the MPETS method is useful for passing on the free flap technique.…”
Section: Discussionmentioning
confidence: 99%
“…18 Another study conducted recently in 2023, in Griffin Institute United Kingdom on 155 health professionals attending a 5-days microsurgery curriculum delivered between 2017 and 2020 reported that increased time duration of training, improved learning outcomes significantly as 88.5% of the participants attained level 2 of Kirkpatrick evaluation model. 19 In a study conducted by Lauciphler MC and his colleagues, pre and post study of a group on Artificial Intelligence was conducted. Post analysis showed significant increase in perceived artificial intelligence readiness.…”
Section: Discussionmentioning
confidence: 99%
“…training. A competent proficiency to reach anastomosis patency may take over ten times of attempts and practice 28 . Therefore, the present study should prompt the microsurgical instructor to pay closer attention to individual suture quality rather than using patency as the gold standard to evaluate the anastomosis success and novice surgeons' skill levels because no relationship exists between the short-term patency and technical errors, except the few mentioned above.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…This study was presented at the Plastic Surgery the Meeting (PSTM) 2021 in Atlanta, Georgia 28 . This article is protected by copyright.…”
Section: Presentedmentioning
confidence: 99%